Complete mitochondrial genomes for Icelus spatula, Aspidophoroides olrikii and Leptoclinus maculatus: pan-Arctic marine fishes from Canadian waters. (3rd July 2016) - Swanburg, Taylor; Horne, John B.; Baillie, Shauna; King, Stanley D.; McBride, Meghan C.; Mackley, Michael P.; Paterson, Ian G.; Bradbury, Ian R.; Bentzen, Paul
Abstract: Three Arctic marine fishes Icelus spatula, Aspidophoroides olrikii and Leptoclinus maculatus have been identified as target species for investigating the effects of ocean warming on population patterns in high-latitude marine habitats around Canada. In preparation for this research, we have resolved whole mitochondrial genome sequences of 16 384, 17 200 and 16 384 bp for each species, respectively. GC content for each species was 47.5%, 44.2% and 45.3%, respectively. Mitogenome gene composition included 13 protein-encoding genes, 2 rRNA and 22 tRNA genes, for I. spatula and L. maculatus, consistent with other teleosts. Only 20 tRNA genes were annotated for A. olrikii, because tRNA-Pro and tRNA-Thr are poorly characterized and aberrantly located in this species.